SOLUBILITY ENHANCEMENT OF POORLY WATER SOLUBLE DRUG USING NATURAL CARRIER : Pharmaceutical Sciences-Pharmaceutics - M.P., RATNAPARKHI; P.D., CHAUDHARI CHAUDHARI (International Journal of Life Science and Pharma Research, 2022)
Atorvastatin calcium is a synthetic lipid-lowering agent. Atorvastatin (ATR) is an inhibitor of 3-hydroxy-3- methylglutaryl-coenzyme A (HMG-CoA) reductase. This enzyme catalyzes the conversion of HMG-CoA to mevalonate, an early and rate-limiting step in cholesterol biosynthesis. According to the biopharmaceutical classification, ATR comes under Class II (low solubility and high permeability). Because of the limited aqueous solubility, it exhibits dissolution rate limited oral absorption. The objective of this investigation was to improve the solubility of the poorly water soluble drug atorvastatin, using solid dispersion (SD) techniques, with Aegel marmelos Gum (AMG) as a hydrophilic carrier. The effect of two variables related to solid dispersions preparation (drug to carrier ratio and method of preparation) were investigated. All the SDs prepared by Microwave induced fusion and Lyophilisation techniques showed remarkable increase in the solubility compared to the pure ATR.The solubility analysis demonstrated highest increase in the solubility of drug observed with ATR-AMG ratio 1:1 by lyophilisation technique. During In Vitro study result obtained that the SD prepared using the Lyohilisation method containing 1:1 ATR-AMG ratio displays faster dissolution rates compared with those prepared using the other that is 98.8±0.09% drug release within 90 min. The SD was characterized using DSC and XRD technique